1989
DOI: 10.1037/0003-066x.44.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Beyond metaphor: The efficacy of early childhood education.

Abstract: Evidence from model preschool education programs is reviewed to determine what impacts quality programs can have on poor children "s intellectual and social competence; evidence from Head Start is reviewed to determine whether preschool programs of national scope have typically produced the same effects as those produced by model programs. Research has shown that both model programs and Head Start have immediate positive impacts on tests of intellectual performance and social competence but that this impact de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
1
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(103 citation statements)
references
References 23 publications
7
92
1
3
Order By: Relevance
“…The cost of moving programs from medium to high quality has not been accurately estimated, nor have there been studies testing whether the benefits of doing so outweigh the costs. Despite numerous calls to conduct cost-benefit analyses, little evidence exists regarding the costbenefit of large-scale center-based care, such as Head Start (Duncan & Magnuson, 2007;Haskins, 1989), or public preschool centers such as the Oklahoma or Boston pre-K programs (Gormley, Gayer, Phillips, & Dawson, 2005;Weiland & Yoshikawa, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The cost of moving programs from medium to high quality has not been accurately estimated, nor have there been studies testing whether the benefits of doing so outweigh the costs. Despite numerous calls to conduct cost-benefit analyses, little evidence exists regarding the costbenefit of large-scale center-based care, such as Head Start (Duncan & Magnuson, 2007;Haskins, 1989), or public preschool centers such as the Oklahoma or Boston pre-K programs (Gormley, Gayer, Phillips, & Dawson, 2005;Weiland & Yoshikawa, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…With some programs, short-term academic benefits decrease over time even if nonachievement outcomes persist (Barnett, 1992(Barnett, , 1995Lazar & Darlington, 1982;White, 1986). Both the Perry Preschool Project and most Head Start programs have exhibited this pattern (Haskins, 1989;McKey et al, 1985). Evaluators have found that achievement benefits disappeared 3 years after students left those programs, but students continued to be less likely to be placed in special education, less likely to be retained in grade, and more likely to graduate than were their nonprogram counterparts (Berrueta-Clement, Barnett, Epstein, & Weikart, 1984;McKey et al, 1985).…”
Section: Enduring Effectsmentioning
confidence: 99%
“…Lesser-quality programs often do not yield the positive effects that high-quality programs do. 37 Weissberg and Greenberg summarize the ''active ingredients'' of effective programs: ''The lasting benefits of early childhood education have been achieved only by high-quality programs characterized by a developmentally appropriate curriculum based on child-related activities, teaching teams that are knowledgeable in early childhood development and receiving ongoing training and supervision, class size limited to fewer than twenty 3-to 5-year-olds with at least two teachers, administrative leadership that includes support of the program, systematic efforts to improve parents as partners in their child's education, as well as sensitivity to the noneducational needs of the child and family, and evaluation procedures that are developmentally appropriate. '' 38 This list includes several important potential protective factors.…”
Section: Early Childhood Programsmentioning
confidence: 99%